A conceptual approach to strategic performance indicators. Issue 4 (9th December 2016) - Dolan, Tom; Walsh, Claire L.; Bouch, Chris; Carhart, Neil J.
Abstract : Effective decision-making for the provision and maintenance of infrastructure systems requires strategic performance indicators aligned with a clear vision of the societal benefits that infrastructure will be expected to enable and systemic awareness of interdependencies between infrastructure sectors. This paper proposes a conceptual outcome-oriented approach to strategic infrastructure performance indicators as a systemic alternative to current approaches which predominantly focus on performance within individual sectors. The conceptual approach proposed aligns performance measures with stated priorities and future aspirations rather than past performance; provides a transparent framework for decision-making; can be applied at a range of scales; and creates an evidence base against which indicator design can be justified and reviewed. Additionally, the conceptual outcome-oriented approach proposed is adaptable for application in other areas of infrastructure decision-making, in particular the development of methodologies to assess what infrastructure will be needed in the future.